Studi Epidemiologi Kejadian Tuberkulosis Paru pada Pasien Hiv di Kabupaten Wonosobo Tahun 2014 - Hardiko, Hardiko; Wahyuningsih, Nur Endah; Adi, M. Sakundarno (Jurnal Kesehatan Lingkungan Indonesia, 2015)
Background: TB-HIV case in Wonosobo district from 1 case happened in 2013 to 14 new cases and the increasing of 3 death cases of TB-HIV in 2014. Furthermore, there are the absence of a figure of person, place and time against opportunistic infections of tuberculosis with HIV in Wonosobo regency that makes it difficult for decision-making.Â This study aims to provide an overview of the epidemiology of pulmonary tuberculosis in people with HIV in Wonosobo. Methods: This study is a descriptive study with cross sectional design, with the primary data (a new case of HIV in 2014) is 48 respondents, and secondary data (a new cases of BTA in 2014) is 308. Results: In this study, HIV prevalence is 6.18 per 100.000 population, or 29.7% of HIV patients are people with TB-HIV, TB-HIV prevalence is 1.41 per 100.000 people, or 3.7% of TB patients are HIV-TB patients. From 48 respondents with HIV, 22.9% of them suffer from TB-HIV (11), 90.9% aged 15-50 years, 66.6% are women, 90.9% were married, 63.6% are high school graduation, 63.6% are IRT, 90.9% are heterosexual, 81.8% are kinfolk contact with TB patients, 81.8% had no contact in the workplace with TB patients, 54.5% live in urban areas, as well as all respondents live in homes that qualifies sanity including population density, ventilation, lighting, humidity, and temperature. Conclusion: HIV patients who have a history of kinfolk contact with a TB patient has a greater possibility of suffering from TB-HIV, as well as the need for further research to determine the factors that cause why the cases of HIV and TB-HIV in Wonosobodistrict in 2014 is more common suffered in housewives and urban areas. Keywords: TB-HIV, Home Environment, Wonosobo district.